Factors associated with willingness to take Pre-Exposure Prophylaxis (PrEP) among high-risk adolescent boys and young men in Masese fishing community, Uganda - Winnie Agwang; Joanita Nangendo; Sherifah Nabikande; Tom Okello; Joan Tusabe; Fred C. Semitala; Simon Kasasa; Joseph K. B. Matovu (Public Library of Science (PLoS), 2023)
Pre-Exposure Prophylaxis (PrEP) is a known HIV prevention strategy for high-risk populations however, some high-risk communities have not yet fully embraced it. We sought to determine willingness to take PrEP and the associated factors among high-risk adolescent boys and young men (ABYM) in Masese fishing community, Jinja district, Eastern Uganda. We conducted a cross-sectional study, between October and November 2020, using a semi-structured questionnaire among ABYM aged 10-24 years in Masese fishing community, Eastern Uganda. We surveyed 479 participants, who had two or more sexual partners with inconsistent or no condom use. We carried out modified Poisson regression analysis to determine factors associated with willingness to take PrEP.Of 479 high-risk ABYM, 86.4% (n = 414) were willing to take PrEP. Confidence in PrEP safety (adj.PR = 1.56; 95%CI: 1.55, 2.24), availability of PrEP in areas easily accessible by ABYM (adj.PR = 1.40; 95%CI: 1.25, 1.57), and perceiving oneself as being at a very high risk of HIV infection (adj.PR = 1.11; 95%CI: 1.03, 1.20) were positively associated with willingness to take PrEP. On the other hand, being unmarried (adj.PR = 0.92; 95%CI: 0.87, 0.98) and earning more than USD 27 a month (adj.PR = 0.92; 95%CI: 0.87, 0.97) were negatively associated with willingness to take PrEP. There was high willingness to take PrEP among adolescent boys and young men in Masese fishing community. Confidence in PrEP safety, access to PrEP in their community and self-perception to be at high risk for HIV acquisition had a positive bearing on willingness to take PrEP while being unmarried and earning more than USD27 had a negative bearing on willingness to take PrEP. These findings suggest a need for target-specific interventions for unmarried men and those earning >USD27.